2017
DOI: 10.1159/000486066
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Facilitates Matrix Metalloproteinase-9-Mediated Myosin Light Chain Kinase Degradation in Pressure Overload-Induced Cardiac Hypertrophy

Abstract: Background/Aims: Angiotensin II (Ang II) has been shown to promote cardiac remodeling during the process of hypertrophy. Myosin light chain kinase (MLCK), a specific kinase for the phosphorylation of myosin light chain 2 (MLC2), plays an important role in regulating cardiac muscle contraction and hypertrophy. However, whether Ang II could facilitate cardiac hypertrophy by altering the expression of MLCK remains unclear. This study aimed to investigate this effect and the underlying mechanisms. Methods: Cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…15,39 In an earlier study, we found that MLCK and p-MLC2 were involved in CH due to their degradation by AngII. 40 The overexpression of cMLCK in cardiac myocytes promotes sarcomere organization, which is an adaptive response to hypertrophic stimuli during early CH, while the knockdown of cMLCK resulted in sarcomeric disorganization. 41 Moreover, the expression level of cMLCK is reduced in animal models of MI.…”
Section: Mir-200c Directly Targeted Mlckmentioning
confidence: 99%
“…15,39 In an earlier study, we found that MLCK and p-MLC2 were involved in CH due to their degradation by AngII. 40 The overexpression of cMLCK in cardiac myocytes promotes sarcomere organization, which is an adaptive response to hypertrophic stimuli during early CH, while the knockdown of cMLCK resulted in sarcomeric disorganization. 41 Moreover, the expression level of cMLCK is reduced in animal models of MI.…”
Section: Mir-200c Directly Targeted Mlckmentioning
confidence: 99%
“…All animals used in this study were postnatal days 1–3 Sprague-Dawley (SD) rats, which were supplied by the Experiment Animal Centre of Wuhan University. We also followed the methods reported in the literature;[ 20 ] NRCMs were isolated from the hearts of SD rat pups on postnatal days 1–3 and were cultured to <98% purity. [ 21 ] Briefly, SD rats were sacrificed by swift decapitation, and the hearts were excised and minced immediately.…”
Section: Ethodsmentioning
confidence: 99%
“…For example, peroxisome proliferator-activated receptors α and γ ligands downregulate the MMP-9 expression in lipopolysaccharide-treated human monocytic THP-1 cells (Shu et al, 2000). Since angiotensin II induces MMP-9 expression and angiotensin II-induced cardiomyocyte hypertrophy is mediated by MMP-9, tissue protective actions by RAS inhibitors may be at least in part by MMP-9 inhibition (Wang, Cheng, et al, 2017). In addition to these agents, suppression of inflammation by lifestyle modification and treatment of diseases results in the decline in inflammatory cells, which are the major source of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 deletion attenuates LV remodeling and dysfunction after transverse aortic constriction (Heymans et al, 2005). The adverse effect of MMP-9 in the pressure-overloaded heart is strengthened by a recent study that demonstrates that angiotensin II facilitates cardiac hypertrophy through MMP-9 activation (Wang et al, 2017).…”
Section: Potential Therapeutic Targets For Cvd and Ckd In The Elderlymentioning
confidence: 99%